Penyuluhan Pentingnya Menjaga Kesehatan dalam Mengkonsumsi Minuman Kemasan pada Remaja di Sekolah SMP Bethany Medan - Simbolon, Pomarida; Surbakti, Angeli Br; Sipayung, Eunice Kristia; Sihaloho, Flower Desma; Hura, Iman Anugrah Selamat; Marbun, Kajol Santa Monica; Silaban, Patricia Tio Gabriella; Simbolon, Rield Rivaldo Benediktus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The risks of soft drink consumption are such as overweight and obesity, dental caries, diabetes, osteoporosis and bone fractures. To prevent this, it is necessary to make efforts to provide health education so that people can control their lifestyle in a better direction. One of the objectives of health education is counseling on the importance of maintaining health in consuming packaged drinks in adolescents at Bethany Junior High School Medan. The result of the counseling that has been carried out on adolescents is to play an active role in counseling activities on the importance of maintaining health in consuming packaged drinks for adolescents at Bethany Junior High School in Medan. The purpose of this counseling activity on the Importance of Maintaining Health in Consuming Packaged Drinks in Adolescents was carried out as an effort to increase knowledge about the importance of maintaining health in consuming packaged drinks. To achieve the purpose of counseling, the methods used are lectures and the provision of health education information about the importance of maintaining health in consuming packaged drinks in adolescents. The results of counseling to teenagers at Bethany Medan Junior High School showed that the average knowledge score before and after health education was carried out had a difference of 2.37 points